(untitled) (JS (JURNAL SEKOLAH), 2024)
Abstract: The purpose of this study was to improve the writing skills of fourth grade students at SD Negeri 101770 Tembung, Percut Sei Tuan District. The method in this research is Classroom Action Research. The actions taken consisted of two (2) cycles. In cycle I, when writing from 28 students, there were 20 students who completed it with a percentage of 71.4%. In cycle II, the number of students who are serious about writing increases, the quality of writing also increases, the choice of words, the use of language rules are getting better. The results of the study showed that there was an increase in Indonesian learning outcomes by using media images, writing assignments for reading textbooks in class IV SD given by the teacher. Keywords: Writing Skills, Image Media, Learning Outcomes Abstrak: Tujuan penelitian ini untuk meningkatkan keterampilan menulis siswa kelas IV SD Negeri 101770 Tembung Kecamatan Percut Sei Tuan. Metode dalam penelitian ini adalah Clasroom Action Research. Tindakan yang dilakukan terdiri dari dua (2) siklus. Pada siklus I, saat menulis dari 28 siswa, terdapat 20 orang siswa yang tuntas dengan persentase 71,4%. Pada siklus II ini jumlah siswa yang serius dalam menulis bertambah, kualitas tulisan juga meningkat, pilihan kata, penggunaan kaidah bahasa semangkin baik. Hasil penelitian menunjukkan bahwa terdapat peningkatan hasil belajar bahasa indonesia dengan menggunakan media gambar, tugas-tugas menulis bacaan buku pelajaran di kelas IV SD yang diberikan oleh guru. Kata kunci : Keterampilan Menulis, Media Gambar, Hasil Belajar Siswa